ANALISIS PESAN PADA PERILAKU HOMOSEKSUAL FILM 2GETHER THE MOVIE - Azizah Aulia; Riki Rikarno (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The aim of this research is to understand what forms of homosexual behavior are found in the film 2gether The Movie. This type of research uses qualitative with a content analysis approach from dialogues between characters that contain forms of homosexual behavior. The data collection technique used is a data analysis technique, which begins by collecting data from the film 2gether, then drawing conclusions. The results of the research show that there are forms of homosexual behavior contained in the film 2gether The Movie. Forms of homosexual behavior include expressions of affection that involve attention and feelings to show love and concern for a partner, while emotional intimacy reflects deep closeness through sharing feelings and experiences. In social settings, homosexual individuals engage in positive and realistic activities with friends and experience normal daily communication and interactions, similar to heterosexual couples. Disclosure of identity and feelings is an important process for building more serious and authentic relationships, allowing individuals to form strong bonds and understand each other.